Immediate versus deferred stenting for patients undergoing primary or emergent percutaneous coronary intervention: Protocol for a systematic review and meta-analysis. Issue 47 (November 2017) - Liu, Yong; Islam, Sheikh Mohammed Shariful; Chow, Clara K.; Chen, Shiqun; Siddiqui, Muhammad Umer; Li, Qiang; Lin, Kai-yang; Wang, Kun; Sun, Guoli; Zhou, Ying-ling; Chen, Jiyan; Brieger, David
Abstract: Introduction: Primary or emergent percutaneous coronary intervention (PCI) with stenting is the standard treatment for patients with ST-segment elevation myocardial infarction (STEMI) or non-STEMI acute coronary syndromes (ACS) at high risk. The value of delayed stenting following balloon-facilitated reperfusion in these patients is largely unknown. Methods and analysis: This systematic review aims to assess whether delayed stenting (vs immediate stenting) improves angiographic and cardiovascular clinical outcomes for patients with STEMI or non-STEMI ACS undergoing primary or emergent PCI. The primary endpoint is adverse angiographic outcomes (no or slow coronary flow after final PCI), the main secondary endpoint includes a composite of long-term (≥6 months) all-cause mortality, recurrent ACS (recurrent myocardial infarction, unplanned revascularization of the target vessel, etc.), hospital admission for heart failure or any other cardiovascular cause. Relevant studies will be searched in the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and other electronic databases. Two authors will independently screen studies for inclusion, consulting with a third author where necessary to resolve discrepancies. The risk of bias of included studies will be assessed using the Cochrane Collaboration risk of bias tool, and quality of evidence using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach. Results will be presented using risk ratios with 95% confidence interval (CI) for dichotomous outcomes and standardized mean differences with 95% CI for continuous outcomes. Ethics and dissemination: This systematic review and meta-analysis protocol will not require ethical approval. We will disseminate the findings of this systematic review and meta-analysis via publications in peer-reviewed journals.